2017
DOI: 10.1590/1807-1929/agriambi.v21n6p404-409
|View full text |Cite
|
Sign up to set email alerts
|

Cassava wastewater as organic fertilizer in ‘Marandu’ grass pasture

Abstract: A B S T R A C TThis study aimed to evaluate the use of wastewater from the cassava processing as organic fertilizer on pastures of Brachiaria brizantha cv. 'Marandu' . The treatments were wastewater doses (0, 15, 30, 60 , which promotes a higher mass of forage and lower of undesirable plants.Água residuária da mandioca como fertilizante orgânico em pasto de capim-marandu

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
1
4
0
2
Order By: Relevance
“…The fractions were placed in previously identified paper bags, weighed on a digital scale and placed in a forced ventilation oven at 55°C for 72h until constant mass. The fractions were then weighed to estimate dry weight of each fraction of the sample in order to estimate dry mass production of each botanical component (Bezerra et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…The fractions were placed in previously identified paper bags, weighed on a digital scale and placed in a forced ventilation oven at 55°C for 72h until constant mass. The fractions were then weighed to estimate dry weight of each fraction of the sample in order to estimate dry mass production of each botanical component (Bezerra et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Cassava wastewater is released during the cassava flour production and is characterized by a high organic load, fibers, starch, cyanogenic compounds and nutrients such as nitrogen, phosphorus, potassium, calcium and magnesium (Araújo et al 2015, Bezerra et al 2017, Sánchez et al 2017. In northeastern Brazil, most cassava wastewater is produced in small facilities and discharged directly into the soil, causing aesthetic and environmental inconveniences in the vicinity of flour mills (Araujo & Lopes 2009, Sánchez et al 2017.…”
Section: Palavras-chavementioning
confidence: 99%
“…Araújo et al (2015), when analyzing the growth and yield of maize fertilized with cassava wastewater doses, reported that this effluent was effective for plant growth. Bezerra et al (2017) used cassava wastewater as a source of organic fertilizer in 'Marandu' palisade grass pasture and observed that the increase of effluent depths promoted a greater forage biomass and reduction of spontaneous plants.…”
Section: Palavras-chavementioning
confidence: 99%
“…(2020) e ARAÚJO et al (2019), afirmam que a manipueira pode ser utilizada como biofertilizante, atenuando assim os efeitos que o lançamento inadequado desse resíduo em corpos hídricos e solo possa vir a provocar. Diversos estudos evidenciam a potencialidade do uso da manipueira na produção agrícola (CARDOSO, 2005;SARAIVA et al, 2007;DUARTE et al, 2012;ARAÚJO et al, 2015;NEVES et al, 2017;RAMOS et al, 2020) e consequentemente nos atributos físicoquímicos do solo (DUARTE et al, 2013;BEZERRA et al, 2017). Neste sentido, o uso SILVA, et al…”
Section: Introductionunclassified